1987
DOI: 10.1128/aem.53.10.2426-2434.1987
|View full text |Cite
|
Sign up to set email alerts
|

Production and Fate of Methylated Sulfur Compounds from Methionine and Dimethylsulfoniopropionate in Anoxic Salt Marsh Sediments

Abstract: Anoxic salt marsh sediments were amended with DL-methionine and dimethylsulfoniopropionate (DMSP). Microbial metabolism of methionine yielded methane thiol (MSH) as the major volatile organosulfur product, with the formation of lesser amounts of dimethylsulfide (DMS). Biological transformation of DMSP resulted in the rapid release of DMS and only small amounts of MSH. Experiments with microbial inhibitors indicated that production of MSH from methionine was carried out by procaryotic organisms, probably sulfat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(76 citation statements)
references
References 44 publications
(58 reference statements)
6
70
0
Order By: Relevance
“…Glutaraldehyde was previously shown to inhibit the cleavage of DMSP to DMS in marsh sediments. However, it did not totally eliminate cleavage [43]. Due to this inhibition, the actual rate of DMS production from DMSP in glutaraldehydekilled cores may have been lower than what occurred naturally.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Glutaraldehyde was previously shown to inhibit the cleavage of DMSP to DMS in marsh sediments. However, it did not totally eliminate cleavage [43]. Due to this inhibition, the actual rate of DMS production from DMSP in glutaraldehydekilled cores may have been lower than what occurred naturally.…”
Section: Discussionmentioning
confidence: 91%
“…Howes et al [10] postulated that DMS increases were due to release of the osmolyte DMSP, which is found in Spartina species [20] and its subsequent cleavage to DMS and acrylic acid. Kiene and Visscher [43] have demonstrated that DMSP rapidly yields DMS when added to anoxic marsh sediments. Thus, DMSP from Spartina plants and detritus may be a major source of DMS in marsh sediments.…”
Section: Discussionmentioning
confidence: 99%
“…DMS is also a suitable substrate for methanogens in marine sediments (Oremland and Polcin 1982;Kiene et al 1986;Giani et al 1996;Lyimo et al 2002), and at high concentrations can be a non-competitive substrate for methanogens (Kiene et al 1986). Kiene (1988) observed that DMS in Spartina sediment slurries contributed to 28% of methane production and 1% or less to dissimilatory sulfate reduction, but at low (1 lM) concentrations, the terminal S-methyl group was metabolized almost exclusively to CO 2 (Kiene and Visscher 1987).…”
Section: Tong Et Almentioning
confidence: 99%
“…The sediment was enriched by the addition of dimethylsulfide as the only catabolic substrate and BES as an inhibitor of methanogenic archaea. BES has been used extensively in various ecological studies especially when studying the interaction of sulfate reduction and methanogenesis (Oremland et al, 1982;King, 1984;Kiene & Visscher, 1987;Lomans et al, 1997). However, after several transfers of the enrichment with dimethylsulfide and BES, it was realized that BES was supporting the growth of contaminants.…”
Section: Enrichment and Isolationmentioning
confidence: 99%
“…In marine systems, they originate mainly from the degradation of dimethylsulfoniopropionate, an osmolyte found in algae and halophilic plant species (e.g. Kiene & Visscher, 1987;Kiene & Taylor, 1988;Kiene, 1990). Emission of volatile organic compounds to the atmosphere is limited because they can be degraded by both aerobic and anaerobic microorganisms.…”
Section: Introductionmentioning
confidence: 99%